Effect of Corporate Governance Rules on Voluntary Disclosure in Jordanian Corporations (An Empirical Study) - AL-NIMER, Munther (Journal of Advanced Research in Law and Economics; Vol 9 No 2 (2018): JARLE Volume IX Issue 2(32) Spring 2018DO - 10.14505//jarle.v9 2(32).01, 2018)
This paper aims to examine the impact of corporate governance (CG) rules using several variables—size of the board of directors, size of the audit committee, family ownership ratio, and their impact on the level of the voluntary disclosure of companies listed with Amman Stock Exchange (ASE). The study was conducted based on the annual reports of the first market that include 55 firms. Content analysis was applied to collect the required data from several sectors (financial, insurance, services, and industrial sectors) from 2016 to 2017.The results indicate a negative association among family ownership ratio, size of the audit committee, and voluntary disclosure level. However, the study shows that the size of the board of directors has a significant positive relationship with the level of voluntary disclosure. Furthermore, the results show that CG rules (size of the board of directors, size of the audit committee, and family ownership ratio) have a significant positive relationship with the voluntary disclosure level of the companies listed with ASE. In the borderline market environment, the study contributes to a theoretical understanding of the corporate governance of voluntary disclosure and the relationship between corporate governance mechanisms and voluntary disclosure. The outcomes provide empirical support for the theoretical notion that effective corporate governance plays an important role in increasing the extent of voluntary disclosure.